Enhancement using external magnetic field on mercury capture by fly ash. (15th December 2015) - He, Ping; Zhang, Xianbing; Peng, Xiaolong; Wu, Jiang; Chen, Naichao; Ren, Jianxin
Highlights: A novel method is proposed by imposing EMF on fly ash to improve mercury capture. EMF increases by 15–25 percentage points of mercury removal capacity for fly ash. Energy level splitting of mercury atom is useful for mercury capture by fly ash. Magnetochemistry effect of fly ash may be benefit for mercury removal. Abstract: Experimental research has indicated that magnetic materials in fly ash can arouse the catalytic oxidative capacity that facilitates mercury capture. In this work, external magnetic field (EMF), rather than magnetic sorbent, is conducted to evaluate the behavior between magnetism and mercury removal. The experimental tests are designed to study the influence of EMF on the mercury adsorption capacity of fly ash. The results show that the mercury removal efficiency of the fly ash with EMF increases by 15–25 percentage points as compared with that without EMF. This enhancement may be a result from energy level splitting of mercury derived from EMF and the magnetochemistry effect of magnetic materials in fly ash.